. Increased systemic exposures of artemether and dihydroartemisinin in infants under 5 kg with uncomplicated Plasmodium falciparum malaria treated with artemether-lumefantrine (Coartem®). - ALAO, Maroufou Jules (My University, 2015)
Background: Artemether-lumefantrine (AL) dispersible formulation was developed for the treatment of uncomplicated Plasmodium falciparum malaria in infants and children weighing 5 to <35 kg. However, there are no clinical studies with artemisinin-based combination therapy in infants <5 kg. Methods: This multicentre, open-label, single-arm study evaluated the efficacy, safety and pharmacokinetics of AL dispersible in infants aged >28 days and <5 kg of body weight, who were treated with one AL dispersible tablet (20 mg artemether/120 mg lumefantrine) given twice-daily for three days and followed up for six weeks (core follow-up) and at 12 months of age (long-term follow-up). Results: A total of 20 patients were enrolled and completed the six-week core study follow-up. In the per protocol population, PCR-corrected cure rate at days 28 and 42 was 100% (95% CI: 79.4, 100). AL dispersible was well tolerated with reported adverse events of mild to moderate severity. Pharmacokinetic data showed that lumefantrine levels were similar, however, artemether and dihydroartemisinin levels were on average two- to three-fold greater than historical values in infants and children ≥5 kg. Conclusions: A three-day regimen of AL dispersible formulation was efficacious and generally well tolerated in infants weighing <5 kg with uncomplicated P. falciparum malaria, but artemether and dihydroartemisinin exposures could not be supported by the preclinical safety margins for neurotoxicity. Hence, dosing recommendations cannot be made in infants <5 kg as implications for toxicity are unknown.
Keywords: Artemether-lumefantrine; Dispersible; Efficacy; Infants; Pharmacokinetics; Safety; <5 kg body weight